PUBLIC PERCEPTION ON REASONS FOR PRACTISING KETOGENIC DIET - KAVIYAS, K.; SREEYA (International Journal of Psychosocial Rehabilitation, 2020)
There has been a sensational resurgence of enthusiasm for the ketogenic diet amid the previous quite a while. For some youngsters with hard to-control epilepsy, the eating regimen exhibits an elective way to deal with attempting various meds. The ketogenic diet's present achievement rate, when legitimately executed, incredibly surpasses that of the prescriptions which have as of late turned out to be accessible. Its reactions, both intellectual and unfavorably susceptible, seem less than most accessible prescriptions. The researcher used descriptive research to do the research. 1860 samples collected using a convenient sampling method. The dependent variables are composition of ketogenic diet, betterment of diet, reasons for practising ketogenic diet such as blood pressure, sugar, fat, abdominal obesity and stress. The research tools used are correlation, chi square and ANOVA. It has been found that there is a low correlation between betterment of ketogenic diet and age. It infers that if the age is high then the people are not bothered about ketogenic diet.